(untitled) (Revista de Estudos da Linguagem, 2024)
This article discusses the design elements of a text composed of six pieces/ cards published by TAG Livros on Instagram on the International Day Against Homophobia, Transphobia and Biphobia, in Brazil, on May 17, 2022. Despite the enormous political and humanitarian relevance of this theme, we will restrict ourselves to the elements that make up the cards, producing a reading exercise of their production and consumption processes, informed by multimodality. The cards, directly selected from the TAG Books Instagram profile, were then downloaded and organized for analysis. The results of this theoretical incursion into the full text, especially informed by the books Multimodal discourse and Reading images, by Kress and Van Leeuwen (2001; 2006), favor questions and reflections about our conceptions of text and design. Also on the agenda are the scope and reach of linguistic studies as well as the linguists’ education, in the face of such complex and, at the same time, socially current objects. Some categories of this approach are debated here, based on the materiality of the selected text. In the final considerations, we ask new questions regarding compositions like the one we focus on here, in addition to proposing a constant exercise of broadening the horizons of linguists and teachers of reading and text production.